Effectiveness of E-Media On SSI To Increasing Students' Scientific Literacy - Meta-Analysis - Usman, Aulia; Suryanti, Suryanti; Supardi, Zainul Arifin Imam (JKTP: Jurnal Kajian Teknologi Pendidikan, 2024)
Science subjects require a variety of learning media as support to make it easier for students to understand the concepts taught. Without the support of the right learning media, science material is often difficult to understand properly. Effective learning media include technology-based interactive media and visual media that help visualize concepts. This study aims to analyze the effect of socio-scientific issues based learning media in improving students' science literacy. The research method used is meta-analysis by reviewing articles from relevant national and international journals. The data were analyzed in the form of students' pretest and posttest results, as well as the N gain test to measure the improvement of science literacy. Quantitative data analysis was conducted to determine the effectiveness of SSI-based learning media on science literacy. Based on the results of the meta-analysis, it indicates that the use of SSI-based media is very effective in improving students' science literacy at various levels of education. Abstrak Mata pelajaran IPA membutuhkan berbagai media pembelajaran sebagai penunjang untuk mempermudah siswa memahami konsep yang diajarkan. Tanpa dukungan media pembelajaran yang tepat, materi IPA sering kali sulit dipahami dengan baik. Media pembelajaran yang efektif meliputi media interaktif berbasis teknologi maupun media visual yang membantu visualisasi konsep. Penelitian ini bertujuan untuk menganalisis pengaruh media pembelajaran berbasis Socio-Scientific Issues dalam meningkatkan literasi sains siswa. Metode penelitian yang digunakan adalah meta-analisis dengan melakukan kajian terhadap artikel dari jurnal nasional dan internasional yang relevan. Data yang dianalisis berupa hasil pretest dan posttest siswa, serta uji N gain untuk mengukur peningkatan literasi sains. Analisis data kuantitatif dilakukan untuk menentukan efektivitas media pembelajaran berbasis SSI terhadap literasi sains. Berdasarkan hasil meta-analisis, mengindikasikan bahwa penggunaan media berbasis SSI sangat efektif dalam meningkatkan literasi sains siswa pada berbagai jenjang pendidikan.